STUDENTS' PERCEPTION ON THE USE OF MOODLE IN ENGLISH LANGUAGE TEACHING DURING COVID-19 PANDEMIC - Achmad Iswanto (Language-Edu, 2021)
The pandemic era has brought changes to every aspect, including the education sector. Distance learning is a role model that is currently used in carrying out teaching and learning activities (KBM). Moodle is present as one of the platforms of choice in facilitating the distance learning process. This study aims to describe students' perception of the use of Moodle in English Language Teaching during covid-19 at the Islamic Institute of Abdullah Faqih Gresik. This study used descriptive quantitative with survey method. Data collection using a questionnaire. Data validation of this study is used SPSS 24. Meanwhile, data analysis is used descriptive statistical analysis by looking for the average data (mean). Subjects in this study are 130 students that are divided into 2nd, 4th, and 6th semesters of the Islamic Insititute of Abdullah Faqih. The result of this study showed that the sub-statement on the ease of usage, the overall average is 3.76 with high rank; sub-statement on Perceived Usefulness, the overall average 3.74 with high rank; sub-statement on communication and interaction, the overall average 3.58 with high rank; sub-on statements Students’ Satisfaction shows average 3.82 with high rank. The researcher also found another finding of several main points that can be taken from student receptions on the application of Moodle in learning English. In general, the student's response to the application of this model is quite good.